Bridging IoT infrastructure and cloud application using cellular-based internet gateway device - Eko Sakti Pramukantoro; Maxi Luckies; Fariz Andri Bakhtiar (Universitas Ahmad Dahlan, 2019)
An Internet of Things (IoT) middleware can solve interoperability problem among “things” in IoT infrastructure by collecting data. However, the sensor nodes’ data that is collected by the middleware cannot be directly delivered to cloud applications since the sensor nodes and the middleware are located in intranet. A solution to this problem is an Internet Gateway Device (IGD) that retrieves data from the middleware in intranet then forwards them to cloud applications in the internet. In this study, an IGD based on cellular network is proposed to provide wide-coverage internet connectivity. Two test scenarios were conducted to measure delay and throughput between the IGD and the cloud application; using data from DHT22 sensor and image sensor respectively. The results of the first test scenario using DHT22 sensor show that the average delay is under 5 seconds and the maximum throughput is 120 bps, while the second one using image sensor concludes that the average delay is 595 seconds and the maximum throughput is 909 bps.